2013
DOI: 10.1111/1556-4029.12366
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Identifying Juvenile/Adult Status from Third Molar Development using Prediction Probabilities Derived from Logistic Regression Analysis

Abstract: The use of third molars in predicting juvenile/adult status ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Different sensitivity and specificity in these populations may be either due to actual differences between them or differences in the age distribution and sample size, as well as dissimilarity among observers. However, the examination of the third molars may provide reasonable accuracy for the likelihood that a person is at least 18 years old (Acharya et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Different sensitivity and specificity in these populations may be either due to actual differences between them or differences in the age distribution and sample size, as well as dissimilarity among observers. However, the examination of the third molars may provide reasonable accuracy for the likelihood that a person is at least 18 years old (Acharya et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Later, Acharya et al 63 applied the grading system of Köhler et al 64 to assess the ability of third molars in determining the age of majority, and summarized that only 35-37% of the sample examined falls into "reliable" prediction of juvenile/adult status, which is just over one in three cases. Based on the allocation accuracies, the author also suggested that Köhler's grading of third molars in Indians may be disadvantageous to individuals <18 years old, because of its tendency in the wrongful prediction of a juvenile as an adult.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, considering all the possible limitations, I3M proved to be able to provide a good accuracy in discerning the individuals under the age of 18 years from the older ones. 11,[19][20][21] It should be remembered also that there are recommendations for age estimation as those of AGFAD (Study Group on Forensic Age Diagnostics) or those of the Forensic Anthropology Society of Europe (FASE); they state that age should be estimated by a forensic expert and that the examination should include a physical examination, a radiography of the no dominant side hand, a dental exam (dental condition and ortopantomographs), and a radiography of medial epiphysis of the clavicle. 11,12,[22][23][24] There is a discordance in the literature regarding the sex difference, in fact, according to some authors it should be considered, since dental mineralization would be premature for men, 25 whereas according to other authors, there are not any particular differences between the two sexes.…”
Section: Discussionmentioning
confidence: 99%